Implicatures in Law: when the law says it without saying it (Revista do Tribunal Regional Federal da 3ª Região, 2025)
This article investigates the applicability of implicatures – what is said without saying – in Law. The objective is to answer whether implicatures are compatible with the legal system, particularly in the interpretation of normative texts. To this end, it employs theoretical-bibliographical research of a qualitative nature. First, it examines the meaning and function of implicatures in ordinary conversational contexts, distinguishing them from related concepts. Next, analyzes the obstacles to their use in legal language, such as the absence of an individual legislator with a single intention and the impossibility of immediately cancelling an implicit meaning, proposing a criterion for their admission based on contextual dependence. The paper formulates two conclusions: (i) particularized implicatures, which depend on a specific and individual context to be understood, are incompatible with the legal system as they violate legal certainty, the separation of powers, and legality; and (ii) generalized conversational implicatures are not only admissible but are binding in the interpretation of normative texts, with no difference in hierarchy or normative effect between explicit and implicit meanings.
Keywords: implicatures; speaker meaning; philosophy of language; context; legal interpretation